INTERACTION EFFECT OF SUSTAINABILITY REPORTING AND ENTERPRISE RISK MANAGEMENT ON BUSINESS PERFORMANCE - Goman, Michael; Daromes, Fransiskus E.; Tangke, Paulus (School of Accountancy, University of Agung Podomoro, 2021)
This study provides empirical evidence of the interaction of sustainability reporting and Enterprise risk management on business performance. A number of previous literatures have found a significant positive effect of ERM implementation on overall business performance, however, the number of studies investigating the interaction of sustainability reporting and ERM is still limited. We build this research model based on modern portfolio theory and stakeholder theory. Data testing was carried out using the moderation regression method in examining the three variable relationships above. The results showed that there was a significant positive effect of ERM on business performance as measured using EVA. Meanwhile, sustainability reporting, although able to strengthen the coefficient of determination relationship between ERM and EVA, does not have a significant moderating effect on the relationship between the two variables.